The Use of Stimulus Preference Assessments to Determine Procedural Acceptability for Participants. (October 2022) - Huntington, Rachelle N.; Schwartz, Ilene S.
The social validity of behavior intervention is rooted in consumer perception. This information is typically garnered through questionnaires and interviews conducted with relevant consumers such as teachers or caregivers. Often, the participants (i.e., the individuals with disabilities receiving the intervention) play less of a role in the assessment of social validity, despite their primary role in intervention. This study examines a procedure for including participants in the assessment of social validity, namely procedural acceptability. Three participants selected their preferred intervention in a paired stimulus preference assessment. Videos presented the intervention options, and participants' preferred interventions were implemented. These interventions decreased target behavior(s) and increased on-task behavior for all participants. The article concludes with a discussion of implications for use of this procedure and considerations for including participants in social validity assessments.